2020
DOI: 10.3390/cancers12020481
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy of Pancreatic Ductal Adenocarcinoma: A Review of the Current Status of Literature

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has long been associated with low survival rates. A lack of accurate diagnostic tests and limited treatment options contribute to the poor prognosis of PDAC. Radioimmunotherapy using α- or β-emitting radionuclides has been identified as a potential treatment for PDAC. By harnessing the cytotoxicity of α or β particles, radioimmunotherapy may overcome the anatomic and physiological factors which traditionally make PDAC resistant to most conventional treatments. Appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Radioimmunotherapy with b-emitters may be less influenced by dense tumor stroma, as cross-fire radiation can treat regions of the tumor unbound by drug. Indeed, radioimmunotherapy research has been vibrant with the recent reemergence of nuclear theranostics, and over 15 preclinical trials testing discrete therapies against targets like CA19.9, MUC1, and integrin a6b4 have shown considerable promise in reducing tumor burden and/or extending overall survival (28). More rigorous comparisons between 4A06 and other experimental therapeutics are warranted to assess the relative strengths and weaknesses of each drug target.…”
Section: Discussionmentioning
confidence: 99%
“…Radioimmunotherapy with b-emitters may be less influenced by dense tumor stroma, as cross-fire radiation can treat regions of the tumor unbound by drug. Indeed, radioimmunotherapy research has been vibrant with the recent reemergence of nuclear theranostics, and over 15 preclinical trials testing discrete therapies against targets like CA19.9, MUC1, and integrin a6b4 have shown considerable promise in reducing tumor burden and/or extending overall survival (28). More rigorous comparisons between 4A06 and other experimental therapeutics are warranted to assess the relative strengths and weaknesses of each drug target.…”
Section: Discussionmentioning
confidence: 99%
“…Astatine-211-OTSA101, an α-emitting anti-FZD10 RIC, suppressed tumor growth of SS mouse xenografts more efficiently than the same dose of the Yttrium-90-OTSA101, a β-emitting anti FZD10 RIC, without remarkable toxic side effects [110]. This confirmed that α-RIT is superior to β-RIT in treating solid tumors because α-particles, with higher linear energy transfer, may have more advantages in terms of cytotoxicity compared to β-particles, with lower linear energy transfer [111].…”
Section: Radioimmunoconjugates For Sarcomamentioning
confidence: 59%
“…A wide range of antibodies have been developed to target MUC1-CE including PAM4, Gatipotuzumab, TAB004, MA5 and C595 (Danielczyk et al 2006 ; Gold et al 2013 ; Wu et al 2018a ; Price et al 1990 ). Radiolabelling of these antibodies to a therapeutic radionuclide which emits alpha particles, beta particles or auger electrons has been shown to elicit a cytotoxic effect (Hull et al 2020b ). This radioimmunotherapy (RIT) approach allows for systemic yet localised targeting of MUC1-CE expressing cells which can be harnessed to treat metastatic disease including micro-metastases.…”
Section: Introductionmentioning
confidence: 99%